Translation of verbal humor in Charlie and the Chocolate Factory movie - Mulyati, Ananda Felin Tri; Nugroho, Andy Bayu (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
The purpose of this study is to identify the different types of verbal humor in the movie Charlie and the Chocolate Factory, classify the translation techniques used to translate the verbal humor in the Indonesian subtitle, and assess the acceptability of the verbal humor translation. This study makes use of both qualitative and quantitative methods. The qualitative method was used to define, classify, and describe the verbal humor types and the translation techniques. Furthermore, the quantitative method was used to assess the translation's acceptability. The data were analyzed by comparing the dialogue transcript from Charlie and the Chocolate Factory with its Indonesian subtitle. The findings show that sarcasm is the most prevalent type of verbal humor. This is consistent with the main character, Willy Wonka, who is highly judgmental and arrogant. The most common translation technique discovered is transfer, which means that the subtitle delivers the verbal humor word for word. The acceptability score of the verbal humor translation is 2.5, indicating that the audience must reread and rethink the humor to understand it. This is not satisfying because it takes the audience's attention away from the movie.Keywords: verbal humor, translation technique, translation quality assessment, sarcasm, movie